The effects of different parity and delivery mode on wheezing disorders in the children—a retrospective cohort study in Fujian, China. (3rd October 2022) - Gao, Haiyan; Miao, Chong; Li, Haibo; Bai, Meng; Zhang, Huijie; Wu, Zhengqin; Li, Wei; Liu, Wenjuan; Xu, Libo; Liu, Guanghua; Zhu, Yibing
Abstract: Background: The relationship between childbirth delivery methods and the risk of wheezing in children remains controversial. Few studies have explored it under different maternal conditions. Objective: To explore the influence of childbirth delivery method on the onset of wheezing in children of different parity. Methods: A total of 21716 patients were included in this retrospective observational study. Multivariable logistic regression was used to analyze the relationship between childbirth delivery method and wheezing in children under 18 years of age in Fujian Province. Results: Wheezing differed statistically based on the child's sex, age, season of onset, parity, jaundice history, and feeding patterns ( P < 0.05). After adjusting for confounding factors, in cases of parity greater than two, the risk of wheezing in cesarean section deliveries was higher than that in vaginal deliveries (OR: 1.107; 95% CI 1.010–1.214). In girls with parity greater than two (OR: 1.179; 95% CI 1.003–1.387) and normal-weight infants with parity greater than two (OR: 1.106; 95% CI 1.003–1.220), the risk of wheezing in cesarean section deliveries was higher. The interaction term between the mode of childbirth and parity was significant in girls ( P = 0.014). Conclusion: The method of childbirth delivery and parity are related to the risk of wheezing and may be relevant to gender and birth weight. Parity and gender have synergistic effects on wheezing.